Stage-specific MCM protein expression in Trypanosoma cruzi: insights into metacyclogenesis and G1 arrested epimastigotes - Santarossa, Bruno Alves; Mariani, Évelin; Corrêa, Artur da Paixão; Costa, Fernanda C.; Taylor, Martin C.; Kelly, John M.; Elias, Maria Carolina; Calderano, Simone Guedes (Frontiers in Cellular and Infection Microbiology, 2025)
Trypanosoma cruzi is a protozoan parasite that is the etiological agent of Chagas disease, which is endemic to Latin America with reported cases in non-endemic regions such as Europe, Asia, and Oceania due to migration. During its lifecycle, T. cruzi alternates between replicative and non-replicative infective lifeforms. Metacyclogenesis is the most studied transition of the T. cruzi life cycle, where replicative epimastigotes differentiate into infective metacyclic trypomastigotes inside the gut of the triatomine vector. This early-branching organism expresses a divergent pre-replication complex (pre-RC) where the only conserved component is the MCM2–7 protein family. Given the role of pre-RC components in cell cycle regulation, we investigated whether MCM expression and location could be involved in proliferation control in epimastigotes and during metacyclogenesis. Using CRISPR/Cas9, we tagged MCM subunits and tracked their expression and subcellular localization. Our findings reveal that MCM subunits are consistently expressed and localized to the nucleus throughout the epimastigote cell cycle, including in G1/G0-arrested cells. However, MCM subunits are degraded during metacyclogenesis as cells enter the G0 state, marking the transition to replication arrest. Therefore, epimastigotes arrested in G1/G0 can either maintain MCM complex expression and resume the cell cycle when conditions become favorable, or they can undergo metacyclogenesis, exiting the cell cycle and entering a G0 state, where MCM subunits are degraded as part of the replication repression mechanism.